BS EN ISO 1833-12. Textiles. Quantitative chemical analysis. Part 12. Mixtures of acrylic, certain modacrylics, certain chlorofibres, certain elastane fibres with certain other fibres (method using dimethylformamide) (22nd April 2020) - British Standards Institution,
No abstract available